Python programming - Sridhar, S.; Indumathi, J.; Hariharan, V. M. (Pearson India Education Services Pvt. Ltd, 2023)
Python Programming is designed as a textbook for undergraduate and postgraduate students to provide programming knowledge and enhance problem solving skills. The book begins with the basics of Python programming followed by the basics of algorithms and further focuses on topics like introduction to programming language, looping, functions, and data structures like lists, tuples, sets, dictionary, and strings. It covers both functional programming concepts such as higher order functions an object-oriented programming concepts such as inheritance and polymorphism.
Includes bibliographical references and index
Keywords: Python (Computer program language); Computer programming; Python (Langage de programmation); Programmation (Informatique); computer programming